RF heating effects in CEST NMR with hyperpolarized ¹²⁹Xe considering different spin exchange kinetics and saturation schemes - Hernandez-Solarte, David; Schröder, Leif (ChemPhysChem, 2025)
Chemical exchange saturation transfer (CEST) improves the sensitivity of NMR but depending on the spin exchange kinetics, it can require substantial RF energy deposition to label magnetization. Potential side effects like RF-induced heating may occur and must be monitored. Here, we explore the parameter space considering not only undesired heating but also efficient CEST build-up (depolarization rate), spectral resolution (line width), and subsequent effects like changes in chemical shifts of CEST responses. We present a systematic study to compare conventional block pulse with shaped-pulse saturation and quantify how the effective average saturation power impacts these parameters. Pulse shape and nominal excitation bandwidth, however, turned out to have little impact on acquired z-spectra and temperature changes. This study illustrates how different exchange kinetics define different regimes of suitable RF power within the dynamic range of fully saturable magnetization from hyperpolarized 129Xe. Temperature-related changes in the resonance frequency of bound spins were also quantified for the two Xe hosts CB6 and CrA-ma and put into context for typically used CEST acquisition parameters, including the stability of the magnetic field.